FOSTERING RESPECT BETWEEN SMOKERS AND NON-SMOKERS IN THE SOCIETY - Nur'aida, Ai; Yusuf Daffa, Muhammad (Journal of English Education and Teacher Trainer, 2024)
The study aims to enhance comprehension and unity between these two groups by examining current literature to find crucial observations and successful actions. This library research explores methods for cultivating mutual respect between those who smoke and those who do not, within the wider social framework. Moreover, the study investigates societal dynamics and the elements that impact respectful interactions by conducting a thorough analysis of scholarly articles, books, and pertinent publications. This study seeks to analyze existing literature in order to offer insightful viewpoints on the role of libraries and information resources in fostering respect and collaboration between smokers and non-smokers in various social contexts. The purpose of the research is to provide information for future efforts and interventions that aim to create a societal environment that is both courteous and inclusive.